Improved multi-objective artificial bee colony algorithm-based path planning for mobile robots - Cui, Qiuyu; Liu, Pengfei; Du, Hualong; Wang, He; Ma, Xin (Frontiers in Neurorobotics, 2023)
Mobile robots are widely used in various fields, including cosmic exploration, logistics delivery, and emergency rescue and so on. Path planning of mobile robots is essential for completing their tasks. Therefore, Path planning algorithms capable of finding their best path are needed. To address this challenge，we thus develop improved multi-objective artificial bee colony algorithm (IMOABC)， a Bio-inspired algorithm-based approach for path planning. The IMOABC algorithm is based on multi-objective artificial bee colony algorithm (MOABC) with four strategies，including external archive pruning strategy, non-dominated ranking strategy，crowding distance strategy, and search strategy. IMOABC is tested on six standard test functions. Results show that IMOABC algorithm outperforms the other three algorithms in solving complex multi-objective optimization problems. We then apply the IMOABC algorithm to path planning in the simulation experiment of mobile robots. IMOABC algorithm consistently outperforms existing algorithms (the MOABC algorithm and the ABC algorithm). IMOABC algorithm should be broadly useful for path planning of mobile robots.